Analysis of methods of formation of transfer price and possibilities of its implementation in the activities of economic entities - Maxmudov Firdavs Raxmonovich (Genius Journals, 2023)
This abstract highlights the analysis of methods for determining transfer prices and explores the potential for their implementation in the operations of economic entities. Transfer pricing refers to the pricing of goods, services, and intangible assets transferred between related entities within multinational corporations. The study focuses on understanding the various approaches and techniques used to establish transfer prices and how they can be effectively applied in practice. The analysis involves a thorough review of relevant literature, including scholarly articles, research papers, and case studies. The goal is to identify the key factors and considerations that influence transfer price determination, such as market conditions, cost structures, legal and regulatory frameworks, and the arm's length principle. By examining the existing body of knowledge and practical experiences, this analysis aims to provide insights and recommendations for economic entities seeking to develop effective transfer pricing strategies.
Keywords: transfer value; local tax; economic entities; market value of property